Functional ecology of congeneric variation in the leaf economics spectrum. Issue 1 (9th September 2019) - Ji, Wenli; LaZerte, Stefanie E.; Waterway, Marcia J.; Lechowicz, Martin J.
Summary: Variation in resource availability can lead to phenotypic plasticity in the traits comprising the world‐wide leaf economics spectrum (LES), potentially impairing plant function and complicating the use of tabulated values for LES traits in ecological studies. We compared 14 Carex (Cyperaceae) species in a factorial experiment (unshaded/shaded × sufficient/insufficient P) to analyze how changes in the network of allometric scaling relationships among LES traits influenced growth under favorable and resource‐limited conditions. Changes in leaf mass per area (LMA) shifted the scaling relationships among LES traits expressed per unit area vs mass in ways that helped to sustain growth under resource limitation. Increases in area‐normalized photosynthetic capacity and foliar nitrogen (N) were correlated with increased growth, offsetting losses associated with mass‐normalized dark respiration and foliar N. These shifts increased the contributions to growth associated with photosynthetic N‐use efficiency and the N : P ratio. Plasticity in LMA is at the hub of the functional role of the LES as an integrated and resilient complex system that balances the relationships among area‐ and mass‐based aspects of gas exchange and foliar nutrient traits to sustain at least some degree of plant growth under differing availabilities of above‐ and below‐ground resources.